Methods for sustainability: Conclusion - Hartz-Karp, J.; Marinova, Dora (2017)
© Janette Hartz-Karp and Dora Marinova 2017. All rights reserved. Since both sustainability and methods are variably understood, the task of suggesting effective ways to best achieve a more sustainable world is a fraught undertaking. The concept of sustainability, regardless of definition, is extraordinary broad, covering geographies - local to global; sectors - environmental, socio-cultural and economic; small scale and large scale. Complicating this further, sustainability is inherently complex and inevitably unpredictable. Similarly, methods range from techniques and approaches to designing alternative worldviews. Given this cornucopia of dimensions, the selection of methods in this book is aimed at resolving key challenges. The methods can be universally applied and are forward-looking rather than reifying our existing modes of unsustainability. Accordingly, this methods book does not attempt to cover all bases. Instead it represents diverse beacons of light and hope in a broad array of possibilities. Each chapter in this book provides either cutting-edge verifiable methods, or poses different ways to think about, understand and achieve a more sustainable world. Considerable theory and practice also underpin the explanations of the methods. The section on making cities more liveable with a reduced carbon footprint includes chapters that are at the forefront of this body of knowledge. Presenting different worldviews of how more sustainable governance could be achieved, our section on governance is far from typical - embracing generic and specific, global and local. Similarly, the chapters on developing a more sustainable economic base suggest different ways for framing and implementing a new thinking, from broad and generic economic frameworks and methods, to local methods to achieve greater socio-economic sustainability. The final section on more sustainable livelihoods and living presents a small but diverse range of ways to improve lives, including ways to achieve behavioural and societal change. Each of these chapters aims to add to our knowledge of how we can rethink and proactively respond to sustainability challenges in ways that can significantly improve living together and into the future within the limits of our ecosystem.